(untitled) (The Peerian Journal, 2025)
This article discusses the highly skilled professionals in the field of television, as well as emerging creators entering the industry. In television, having high potential and refined taste plays a significant role. The results show that, in television, the teacher-student tradition and the acquisition of knowledge in the field is crucial to mastering the craft.